Verification Of Non-Isolated Lcc Resonant Full Bridge Dc-Dc Converter For Solar Photovoltaic Systems - Teoh , Voon Min (2015)

(untitled)
Awareness about global warming and fasting depleting fossil fuels has intensified researcher’s interest toward exploration of renewable energy resources. Among these renewable resources, photovoltaic (solar energy) is getting more attention because of its potential to be the greatest contributor of electrical energy generation. Generally DC-DC converters are used to interface solar panels with inverter which converters dc power to ac. The function of dc-dc converter is basically to step up the low dc voltage to desired higher output voltage level. Conventional switch mode dc-dc converters have problems of high switching loss and EMI. Resonant converters on the other hand have low switching loss and EMI when they operate under ZVS conditions. The aim of this research work is to explore the feasibility of a non-isolated series-parallel resonant dc-dc converter for application in PV systems. Accordingly, the working action, analysis and design procedure of series-parallel resonant full-bridge dc-dc converter is described in detail. To evaluate the performance of converter both simulation and experimental studies are carried out. First of all, converter is simulated using LT-Spice to evaluate the capability of converter to step-up dc voltage from 30V to 300V. It is shown that converter can provide desired voltage gain both for nominal and light loads with theoretical maximum efficiency up to 94%. Finally a low power laboratory prototype of the converter is built to test and evaluate the performance of the converter. The experimental results show promising performance of the converter up to 88% efficiency at 75 kHz resonance frequency. Therefore, this converter is suitable for application in PV systems where galvanic isolation is not necessary.